Problem of social continuity in society’s development in the hi-tech era - Абисова, М. А. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2017)
The article considers the specificity of social memory as a set of socio-cultural means and institutions that select and rotate relevant social information to the retrospective in order to preserve the accumulated social experience and transfer it from generation to generation in a high-tech society.